SUPPLAY EKSITASI OUTPUT GENERATOR 300 MW MENGGUNAKAN METODE POLA TITIK DAYA REAKTIF - Irwan anto Mina; Mokh. Sidqi Fahmi (Journal of Mechanical Engineering and Mechatronics, 2020)
Excitation system is a system that conducts electric current in the same direction as a generator in a power plant, so that it produces electricity and a large voltage on the increase in the excitation current. In modern regulatory systems, excitation plays an important role in controlling the stability of a development because it involves load fluctuations, so excitation as a controller will require control of the generator output such as voltage, current and power factors in a necessary manner. If the excitation current rises, the reactive power supplied by the system generator will increase otherwise if the reactive power supplied will decrease. If the given excitation current is too small, the reactive power flow will move from the system to the generator so that the generator absorbs the reactive power from the system. This situation is very dangerous because it will cause excessive savings on the stator.Keywords: Generator, excitation system, transformer, rectifier.